Finite Element Analysis of DSSI Effects for a Building of Strategic Importance in Catania (Italy). (2016) - Abate, Glenda; Massimino, Maria Rossella; Romano, Salvatore
Abstract: Structural response to earthquakes has to be definitely considered a multidisciplinary subject, depending on many factors among which local site effects and dynamic interaction between soil, foundations and structures. The present paper deals with the multidisciplinary Dynamic Soil Structure Interaction (DSSI) analysis concerning the INGV building in Catania (Italy) by means of FEM 2D modelling. The building is a masonry structure situated in an area characterized by a high seismic hazard. The dynamic analysis was performed by adopting seven different accelerograms, scaled at the same PHA with reference to the estimated seismicity of the investigated area. Linear visco-elastic constitutive models were adopted for both the soil and the structure; nevertheless, soil non-linearity is taken into account according to EC8, adopting degraded shear modulus and increased damping ratio. The dynamic response of the system was analysed in the time and frequency domains. The main goals of the paper are: i) to investigate the amplification input effects, considering and not considering the DSSI; ii) to highlight the influence of soil layer variation in the coupled system response; iii) to compare the obtained results with the ones given by simpler 1D free-field soil analyses; iv) to compare the acceleration spectra obtained by 1D and 2D analyses with those provided by Italian technical code, NTC08. The performed analyses show the influence of DSSI in the seismic response of the system in terms of PHA and frequency contents.